Constitutional Changes in the Perspective of Legal Philosophy - Yunus, Nur Rohim (ADALAH, 2023)
This essay discusses constitutional change from the perspective of legal philosophy, focusing on philosophical, sociological, and legal aspects. Constitutional change is considered essential to maintain the relevance of a country's fundamental law. This essay reviews the debate between rigid and living constitutions, reflecting the tension between legal stability and flexibility. From the perspective of legal philosophy, constitutional change is analysed through the concepts of justice, utilitarianism, and social contract theory, which emphasise that change must create justice and reflect social consensus. Sociologically, this essay highlights factors such as demographic changes, developments in social values, and interest group pressures that drive constitutional change. From a legal perspective, this essay emphasises the importance of a legitimate amendment procedure to maintain legitimacy. Overall, this essay suggests that constitutional change should be carried out carefully to remain relevant to the dynamics of society without damaging the legal order.